The implications of and institutional barriers to compact land development for transportation: Evidence from Bejing - Zhao, Pengjun (Journal of Transport and Land Use, 2013)
Land use patterns are believed to affect transportation, while low-capacity land-use management is often seen as one of the primary institutional barriers to sustainable transport. Examining the case of Beijing, this paper aims to contribute more evidence in relation to these issues. Over the past decades China’s megacities have witnessed a dramatic transition in land use from traditional compact development to sprawling development due to rapid urbanization. This study found that this transition has tended to increase car usage and thus worsen the emission of pollutants by transport in Beijing when growth of income and other socioeconomic factors are taken into account. It is apparent that compact land-use policies need to be reintroduced to reduce car use. However, there are several institutional barriers related to the reintroduction of compact development in the current context of transition from a centrally planned system to a market system in China’s cities. In particular, increasing fragmentation in the realm of land-development management has created serious challenges to the implementation of compact land-development policies. Therefore, institutional capacity building is needed to enable compact land-use policies to control local sprawl and promote sustainable transport.